Religious, Cultural, and Artistic Tourism in Sustainable Tourism - Muhamad; Dicky Sopjan (PT FORMOSA CENDEKIA GLOBAL, 2022)
The main purpose of this study is to assess the existence of a diversity of religious, cultural, arts tourism and tourist destinations into sustainable tourism products with the criteria of tourism protection, the arts and culture of the local community in a directed and integrated manner in order to realize certain goals dynamically and selectively. Religious, artistic, and cultural tourism have criteria with an assessment of the level of importance and level of quality based on indicators and supporting evidence that forms the criteria. The study method is carried out through qualitative descriptive by revealing events or facts, circumstances, phenomena, variables and circumstances that occur in tourist destinations to make descriptions, descriptions, systematically, factually and accurately regarding facts, characteristics and relationships between phenomena that occur. destinations by level of importance and level of quality. The results of the discussion on management in destinations related to indicators: a) religious, artistic, cultural and natural sites tourism b) religion, culture, and the arts of local communities, c) historic buildings d) rural landscapes, have value at the level of importance and a high level of quality as a product sustainable tourism in Magelang district. Cultural and artistic tourism landscapes have a high level of importance and quality in Magelang Regency as a sustainable tourism product.